Assessment of cerebrovascular function in patients with sickle cell disease using transfer function analysis. Issue 19 (5th October 2022) - Sayin, Ece Su; Sobczyk, Olivia; Poublanc, Julien; Mikulis, David J.; Fisher, Joseph A.; Kuo, Kevin H. M.; Duffin, James
Abstract: In patients with sickle cell disease (SCD), the delivery of oxygen to the brain is compromised by anemia, abnormal rheology, and steno‐occlusive vascular disease. Successful compensation depends on an increase in oxygen supply such as that provided by an increase in cerebral blood flow (CBF). We used magnetic resonance imaging to provide a high‐resolution assessment of the ability of SCD patients to respond to a vasoactive stimulus in middle, anterior, and posterior cerebral artery territories for both white and gray matter. Cerebrovascular reactivity (CVR) was measured as the blood oxygen level dependent signal (a surrogate for CBF) response to an increase in the end tidal partial pressure of CO2 (PET CO2 ). The dynamic aspect of the response was measured as the time constant of the first order response kinetics (tau). To confirm and support these findings we used an alternative examination of the response, transfer function analysis (TFA), to measure the responsiveness (gain), the speed of response (phase), and the consistency of the response over time (coherence). We tested 34 patients with SCD and compared the results to those of 24 healthy controls participants. The results from a three‐way ANOVA showed that patients with SCD have reduced CVR ( p  < 0.001) and lower coherence ( p  < 0.001) in gray matter and white matter and reduced gain in gray matter only ( p  < 0.001). In terms of the speed of the response to CO2, tau ( p  < 0.001) and TFA phase ( p  < 0.001) were increased in SCD patients compared to healthy control subjects. These findings show that the cerebrovascular responsiveness to CO2 in patients with SCD is both decreased and slowed compared to healthy controls. Abstract : We used magnetic resonance imaging to provide a high‐resolution assessment of the ability of sickle cell disease patients to respond to a vasoactive stimulus in middle, anterior and posterior cerebral artery territories for both white and grey matter. Our findings show that the cerebrovascular responsiveness to carbon dioxide in these patients is both decreased and slowed compared to healthy controls.